Compulsão alimentar periódica em mulheres com obesidade grave: prevalência e fatores associados - Melo , Paulla Guimarães (2013)
Introduction: The binge eating (BE) is a prevalent disorder in obese women, with a negative impact on weight loss. Objective: To investigate the prevalence of BE and assess factors associated with severe obese women. Methods: Cross-sectional study with adult women (20-59 years), body mass index (BMI) ≥ 35 kg/m2, who sought treatment for weight loss in Outpatient Nutrition Obesity Grave (ANOG/ HC/ UFG) from February 2008 to June 2012. The variables studied were: sociodemographic (age, marital status, years of education and family income), health conditions (co-morbidities and current medications for weight loss); history of obesity (onset of obesity, obesity in the family and previous treatment for weight loss), lifestyle (physical activity, smoking, alcohol consumption), feeding behavior (number of meals per day habit of pinching, CAP) and anthropometric data (weight, height and BMI). The outcome variable was the presence of BE, determined by applying the Binge Eating Scale. Described themselves frequencies, prevalences and prevalence ratios, considering confidence intervals of 95%. To analyze the association was used Chi-square or Fisher. For values of p <0.20 in the bivariate analysis performed multivariate analysis using Poisson Regression. Considered a significance level of 5%. Results: We analyzed 94 women with a mean age of 37.7 years and mean BMI of 47.4 kg/m². A prevalence of 53.2% in BE, with 28.7% classified as moderate BE and 24.5% as severe BE. Statistically significant associations were observed for age 40-49 years, who presented a 2 times more (p = 0.011) prevalence of BE in relation to the age group of 30 to 39 years and have a habit of snacking which showed 1.9 times higher (p = 0.003) prevalence of BE. Conclusion: Given the high prevalence of BE observed and associated factors, we emphasize the importance of diagnosis and monitoring of BE in severe obese by the multidisciplinary team in order to assist in the effectiveness of dietary treatment.